Identification of candidate genes associated with leaf senescence in cultivated sunflower (Helianthus annuus L.) - Moschen, Sebastian (2014)
Cultivated sunflower (Helianthus annuus L.), an important source of edible vegetable oil, shows rapid onset of senescence, which limits production by reducing photosynthetic capacity under specific growing conditions. Carbon for grain filling depends strongly on light interception by green leaf area, which diminishes during grain filling due to leaf senescence. Transcription factors (TFs) regulate the progression of leaf senescence in plants and have been well explored in model systems, but information for many agronomic crops remains limited. Here, we characterize the expression profiles of a set of putative senescence associated genes (SAGs) identified by a candidate gene approach and sunflower microarray expression studies. We examined a time course of sunflower leaves undergoing natural senescence and used quantitative PCR (qPCR) to measure the expression of 11 candidate genes representing the NAC, WRKY, MYB and NF-Y TF families. In addition, we measured physiological parameters such as chlorophyll, total soluble sugars and nitrogen content. The expression of Ha- NAC01, Ha-NAC03, Ha-NAC04, Ha-NAC05 and Ha-MYB01 TFs increased before the remobilization rate increased and therefore, before the appearance of the first physiological symptoms of senescence, whereas Ha-NAC02 expression decreased. In addition, we also examined the trifurcate feed-forward pathway (involving ORE1, miR164, and ETHYLENE INSENSITIVE 2) previously reported for Arabidopsis. We measured transcription of Ha-NAC01 (the sunflower homolog of ORE1) and Ha-EIN2, along with the levels of miR164, in two leaves from different stem positions, and identified differences in transcription between basal and upper leaves. Interestingly, Ha-NAC01 and Ha-EIN2 transcription profiles showed an earlier up-regulation in upper leaves of plants close to maturity, compared with basal leaves of plants at pre-anthesis stages. These results suggest that the H. annuus TFs characterized in this work could play important roles as potential triggers of leaf senescence and thus can be considered putative candidate genes for senescence in sunflower.